2008
DOI: 10.1371/journal.pntd.0000265
|View full text |Cite
|
Sign up to set email alerts
|

Acute Schistosoma mansoni Infection Increases Susceptibility to Systemic SHIV Clade C Infection in Rhesus Macaques after Mucosal Virus Exposure

Abstract: BackgroundIndividuals living in sub-Saharan Africa represent 10% of the world's population but almost 2/3 of all HIV-1/AIDS cases. The disproportionate HIV-1 infection rates in this region may be linked to helminthic parasite infections that affect many individuals in the developing world. However, the hypothesis that parasite infection increases an individual's susceptibility to HIV-1 has never been prospectively tested in a relevant in vivo model.Methodology/Principal FindingsWe measured whether pre-existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 29 publications
4
73
0
Order By: Relevance
“…Studies in macaques showed that the rectal inoculum of SHIV required for SHIV acquisition was 17 times lower in macaques with than without S. mansoni infection. 4 In contrast, prior S. mansoni infection did not significantly change the required infectious dose when SHIV was inoculated intravenously. 4,27 Researchers postulated that S. mansoni infection increased the number of activated CD4+ T cells in the gut-associated lymphoid tissue (GALT) and thereby increased the optimal targets for SHIV infection.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies in macaques showed that the rectal inoculum of SHIV required for SHIV acquisition was 17 times lower in macaques with than without S. mansoni infection. 4 In contrast, prior S. mansoni infection did not significantly change the required infectious dose when SHIV was inoculated intravenously. 4,27 Researchers postulated that S. mansoni infection increased the number of activated CD4+ T cells in the gut-associated lymphoid tissue (GALT) and thereby increased the optimal targets for SHIV infection.…”
Section: Discussionmentioning
confidence: 96%
“…4 In contrast, prior S. mansoni infection did not significantly change the required infectious dose when SHIV was inoculated intravenously. 4,27 Researchers postulated that S. mansoni infection increased the number of activated CD4+ T cells in the gut-associated lymphoid tissue (GALT) and thereby increased the optimal targets for SHIV infection. Mouse models of schistosomiasis show that S. mansoni eggs induce a Th17 CD4+ T-cell response in the gut mucosa.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1 The waterborne parasite is co-endemic with human immunodeficiency virus (HIV) infection and several studies have suggested an association between the two diseases. [2][3][4][5][6] The lower female reproductive tract is the main site of HIV-1 transmission, and is also the predilection site for female genital Schistosoma haematobium ova deposition. [7][8][9] Similar to sexually transmitted infections (STIs), it has been suggested that genital lesions caused by S. haematobium ova may provide points of entry for HIV.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 It has been suggested that schistosomiasis could be responsible for increased susceptibility to HIV, and a study in Zimbabwe reported a 3-fold higher odds ratio for HIV seropositivity in women with genital schistosomiasis, compared to those without. [7][8][9] This raises the possibility that treatment and prevention of genital schistosomiasis may have an impact on HIV transmission in areas where both infections are prevalent. Improvements in the detection of genital schistosomiasis would be an important component of such a strategy.…”
Section: Introductionmentioning
confidence: 99%